Unveiling the effect of shapes and electrolytes on the electrocatalytic ethanol oxidation activity of self-standing Pd nanostructures - Adewale K., Ipadeola (2023)
Morphologically controlled Pd-based nanocrystals are the most efficient strategies for improving the electrocatalytic ethanol oxidation reaction (EOR) performance; however, their morphological-EOR activity relationship and effect of electrolytes at a wide pH range are still ambiguous. Here, we have synthesized porous self-standing Pd clustered nanospheres (Pd-CNSs) and Pd nanocubes (Pd-NCBs) for the EOR in acidic (H2SO4), alkaline (KOH), and neutral (NaHCO3) electrolytes compared to commercial spherical-like Pd/C catalysts. The fabrication process comprises the ice-cooling reduction of Pd precursor by sodium borohydride (NaBH4) and l-ascorbic acid to form Pd-CNSs and Pd-NCBs, respectively. The EOR activity of Pd-CNSs significantly outperformed those of Pd-NCBs, and Pd/C in all electrolytes, but the EOR activity was better in KOH than in H2SO4 and NaHCO3. This is due to the 3D porous clustered nanospherical morphology that makes Pd active centers more accessible and maximizes their utilization during EOR. The EOR specific/mass activities of Pd-CNSs reached (8.51 mA/cm2/2.39 A/mgPd) in KOH, (2.98 mA/cm2/0.88 A/mgPd) in H2SO4, and (0.061 mA/cm2/0.0083 A/mgPd) in NaHCO3, in addition to stability after 1000 cycles. This study affirms that porous 3D spherical Pd nanostructures are preferred for the EOR than those of 0D spherical-like and multi-dimensional cube-like nanostructures.